The Novel Transcription Factor BnaA01.KAN3 Is Involved in the Regulation of Anthocyanin Accumulation Under Phosphorus Starvation - Li He; Shan Peng; Ruihua Lin; Jiahui Zhang; Peng Cui; Yi Gan; Hongbo Liu (Plants, 2025)
The investigation of phosphorus metabolism and regulatory mechanisms is conducive to maintaining stable production of crops within a low-phosphorus environment. In phosphorus signal transduction, a few phosphorus starvation response (PHR) transcription factors were identified to bind to the characteristic cis-element, namely the PHR1 binding sequence (P1BS). While the molecular function of the PHR transcription factor has been intensively elucidated, here, we explore a novel transcription factor, BnaA01.KAN3, that undergoes specific binding to the P1BS by yeast one-hybrid and electrophoretic mobility shift assays, and its expression is induced with low-phosphorus stress. BnaA01.KAN3 possessed transcriptional activation and was located in the nucleus. The spatiotemporal expression pattern of BnaA01.KAN3 exhibited tissue specificity in developmental seed, and its expression level was especially high 25–30 days after pollination. Regarding the phenotype analysis, the independent heterologous overexpression lines of BnaA01.KAN3 in Arabidopsis thaliana exhibited not only significantly longer taproots but also an increased number of lateral roots compared to that of the wild type undergoing low-phosphorus treatment, while no differences were seen under normal phosphorus conditions. Furthermore, these lines showed higher anthocyanin and inorganic phosphorus contents with normal and low-phosphorus treatment, suggesting that BnaA01.KAN3 could enhance phosphorus uptake or remobilization to cope with low-phosphorus stress. In summary, this study characterized the transcription factor BnaA01.KAN3 that modulates low-phosphate adaptation and seed development, providing insights for improving phosphorus use efficiency and yield traits in Brassica napus.